Environmental stress and grain yields in China - Huang, Jikun; Rozelle, Scott (Wiley, 1995)
After 1984 China's grain production began to stagnate, slowing during a time of continuing expansion of chemical inputs, irrigated area, and high‐yielding rice, wheat, and maize varieties. In this paper we explore the hypothesis that the accumulation of environmental pressures, including erosion, salinization, soil exhaustion, and degradation of the local environment, may be partially responsible for the recent slowdown of grain yields. Using provincial production data from 1975 to 1990, the analysis shows that environmental factors, especially the breakdown of the environment, did contribute to the decline in the rate of increase of yields in China during the late 1980s. Erosion and salinization had a small, negative effect on yields.